Camp zero : a novel - Sterling, Michelle Min, 1982- (Atria Books, 2023)
"In a near-future northern settlement, the fate of a young woman intertwines with those of a college professor and a collective of women soldiers in this mesmerizing and transportive novel in the vein of Station Eleven and The Power. In the far north of Canada, a team led by a visionary American architect is building a project called Camp Zero. With its fresh, clean air and cold climate, it's intended to be the beginning of a new community and a new way of life. A brilliant and determined young woman employed as a sex worker to the elite is offered a chance to join the Blooms, a group meant to service the men in camp-but her mission is to secretly monitor the mercurial architect in charge. In return, she'll receive a home for her displaced Korean immigrant mother and herself. Upon arrival at Camp Zero, she is named Rose. Rose quickly secures the trust of her target, but in the camp, everyone has an agenda, and her alliances begin to shift. Through skillfully braided perspectives, including those of a young professor longing to escape his wealthy family and an all-woman military brigade struggling for survival at a climate research station, the fate of Camp Zero and its inhabitants reaches a stunning crescendo. An electrifying page-turner where nothing is as it seems, Camp Zero cleverly explores how the intersection of gender, class, and migration will impact who and what will survive in a warming world"--